Governing for Future Generations: How Political Trust Shapes Attitudes Towards Climate and Debt Policies - Fairbrother, Malcolm; Arrhenius, Gustaf; Bykvist, Krister; Campbell, Tim (Frontiers in Political Science, 2021)
Policy decisions, and public preferences about them, often entail judgements about costs people should be willing to pay for the benefit of future generations. Economic analyses discount policies’ future benefits based on expectations about increasing standards of living, while empirical studies in psychology have found future-oriented people are more motivated to protect the environment. In this article, using original surveys and survey experiments in four countries—Sweden, Spain, South Korea, and China—we show that support for future-oriented policies also strongly reflects people’s political trust. Focusing on policies for reducing either global warming or public debt, we find political trust operates on attitudes by shaping people’s (a) confidence in policies’ effectiveness and (b) willingness to sacrifice for others. The influence of political trust outweighs that of subjective concern, while discounting has so little impact that people who expect future generations to be richer are more, not less, willing to sacrifice.